IRON AND Α-SYNUCLEIN: HALLMARK OF Α-SYNUCLEINOPATHIES - Sudeepa Srichandan1*, A.K. Panda2, Pratima Ray3 (Chelonian Research Foundation, 2023)
Protein aggregation studies have presented amyloid aggregates as pathological agents responsible for several diseased conditions. structures are difficult to degrade, that’s may be the reason why amyloid deposits cannot be removed by the proteasome system of the cell (1). Deposition of misfolded oligomeric proteins having cross- structure is a characteristic feature of a large number of disorders, collectively called “conformational diseases” (2,3,4). These diseases also known as Amyloidosis includes Alzheimer’s disease (AD), Parkinson’s disease (PD), Spongiform encephalopathies, Type-2 diabetes mellitus, Amyotrophic lateral sclerosis, Huntington’s disease, systemic amyloidosis and all diseases caused by prion proteins (5,6). In recent years, number of studies has shown that the intermediates (oligomers, protofibrils) and not the final mature fibrils display toxicity (7). The amyloid fibril formation follows a nucleated growth mechanism. The nucleation phase is slow in which a nuclei is formed, followed by a fast elongation phase where the partially folded molecules of the protein or oligomers are formed, which binds to the nuclei forming amyloid fibrils (8,9). All amyloid-like proteins display a variety of common features like template-driven propagation, disruption of cellular defence mechanisms, mislocalisation of aggregated protein and glia-mediated neurotoxicity. (10) The structural analysis of these oligomeric species is difficult because of its unstable nature and they are short lived.